2000
DOI: 10.4102/jsava.v71i2.692
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on some reproductive parameters of German shepherd bitches in Kenya : research communication

Abstract: Data relating to reproductive parameters of German shepherd bitches were collected from registered German shepherd dog (GSD) breeders with information kept over a 15-year period (1982-1997). The information obtained was verified using the East African Kennel Club records. A total of 594 bitches from 280 breeders were recorded. From these, 798 heats were observed, 594 of which were used for breeding, resulting in 3592 puppies. The mean age at puberty was 519.0 ± 41 days. Heats occurred throughout the year, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 7 publications
5
19
2
Order By: Relevance
“…In our study, the inter-estrus interval in Kunming dogs was approximately 204 days. This statement agreed with previous studies that pregnancy significantly disrupts the regularity of estrus and lengthens the inter-estrus period (Linde-Forsberg & Wall en 1992;Hoffmann et al 1996;Mutembei et al 2000). Previous studies showed that considerable variations exist in inter-estrus length in an individual animal (Prole 1973;Sokolowski et al 1977;Bouchard et al 1991), although less variability is apparent within animals than within breeds (Stabenfelt & Sbille 1977).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the inter-estrus interval in Kunming dogs was approximately 204 days. This statement agreed with previous studies that pregnancy significantly disrupts the regularity of estrus and lengthens the inter-estrus period (Linde-Forsberg & Wall en 1992;Hoffmann et al 1996;Mutembei et al 2000). Previous studies showed that considerable variations exist in inter-estrus length in an individual animal (Prole 1973;Sokolowski et al 1977;Bouchard et al 1991), although less variability is apparent within animals than within breeds (Stabenfelt & Sbille 1977).…”
Section: Discussionsupporting
confidence: 90%
“…Litter size, maternal parity (Tønnessen et al 2012) and birth weight were also considered as factors involved in neonatal mortality in dogs. Therefore, the mating rate (75%) and pregnancy rate (79.42%) were apparently low compared with rates in other studies (Mutembei et al 2000;England et al 2009). Although the factors controlling this high rate of perinatal loss may be complex, puppy mortality can be reduced by proper management of the whole reproductive process and especially by proper assistance at birth and during the early neonatal period (Davidson 2003).…”
Section: Discussioncontrasting
confidence: 56%
“…The age was another factor that affected the cycle interval; as the age advanced, the cycle interval shortened by 16% in the current study. Conversely, previous studies reported a positive correlation between age and cycle interval (7,8,20,21).…”
Section: Effect ---------------------------P < ----------------------mentioning
confidence: 62%
“…Studies from different regions of the world reported various pregnancy rates, ranging from 64% to 95% (7,10). It was reported to be 64.4%, 85.0%, and 78.6% in a tropical region (10), in England (18), and in Sweden (8), respectively.…”
Section: Effect ---------------------------P < ----------------------mentioning
confidence: 99%
See 1 more Smart Citation